A silicon oxide-based negative electrode material and its preparation and application

By bombarding nitrous oxide plasma and forming a carbon coating layer on the silicon oxide powder, the structural instability of silicon anode material due to volume expansion and contraction in lithium-ion batteries is solved, and the cycle life and safety of the battery are significantly improved.

CN119240709BActive Publication Date: 2025-03-18ANHUI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411729534.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The silicon negative electrode material is structurally unstable due to volume expansion and contraction in lithium-ion batteries, affecting the cycle life and safety of the battery.

Method used

By bombarding the silicon oxide powder with nitrous oxide plasma, a porous structure with N atoms on the surface is formed, and two dense carbon coatings are generated on the surface to enhance the structural integrity of the material.

Benefits of technology

The dense carbon cladding effectively alleviates the stress caused by volume changes, improves the conductivity and lithium storage capacity of the negative electrode material, extends the cycle life of the battery and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicon oxide-based negative electrode material and its preparation and application, belonging to the technical field of lithium ion battery preparation, comprising the following steps: nitrous oxide plasma bombards pure silicon oxide powder to form modified porous silicon oxide powder with N attached, wherein the porosity can accommodate more lithium ions for embedding and de-embedding, and also helps to alleviate the volume effect of the material in the electrochemical reaction process, thereby extending the cycle life of the battery, and at the same time, the N element is doped in the generated carbon layer, thereby improving the conductivity and lithium storage capacity; the two coating layers prepared by the invention form a dense carbon coating layer after high-temperature carbonization, thereby enhancing the structural integrity of the silicon oxide negative electrode material in the charging and discharging process, and in the process of embedding and de-embedding of lithium ions, the dense carbon coating layer can effectively alleviate the stress caused by volume change and reduce the repeated generation and rupture of SEI film, thereby improving the initial coulomb efficiency and helping to maintain the capacity and performance stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery preparation, and specifically relates to a silicon oxide-based negative electrode material and its preparation and application. Background Art

[0002] When used as a negative electrode material, silicon exhibits a series of unique advantages and characteristics. Silicon negative electrode material has an extremely high theoretical capacity, which enables the silicon negative electrode to store more energy, thereby increasing the battery's range or the energy density of the energy storage system. After the first lithium insertion, the structure of the silicon negative electrode material will change to an amorphous state and maintain this form during subsequent cycles. This structural stability helps to extend the cycle life of the battery. During the electrochemical deintercalation of lithium in the silicon negative electrode, its discharge platform is slightly higher than that of carbon materials, and is not prone to the formation of lithium dendrites on the electrode surface, which helps to improve the safety and stability of the battery.

[0003] At the same time, silicon also faces some challenges when used as a negative electrode material. Due to the existence of covalent bonds, the electrons in the silicon crystal are tightly bound around the atoms and cannot move freely, so the conductivity of silicon is poor; the lithium insertion process is an alloying reaction, and the charging and discharging process is accompanied by huge volume changes, with a change rate greater than 300%. The expansion coefficient of silicon oxide is slightly lower than that of single silicon, reaching 110%, which is much higher than the mainstream graphite negative electrode. In the process of repeated insertion and extraction of ions, the material will still crack and powder due to the large volume expansion, which greatly affects the cycle stability of the silicon oxide material.

[0004] Chinese patent application CN116081632A discloses a magnesium-doped silicon oxide composite negative electrode material and a preparation method thereof, wherein silicon oxide fine powder and metal magnesium powder are stirred and mixed evenly to obtain a coating layer. This method is physically doped, the coating is incomplete, and the structure is incomplete and it is difficult to buffer the volume expansion effect. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of forming a porous structure doped with N atoms on the surface by bombarding silicon oxide powder with nitrous oxide gas plasma, and generating two layers of dense carbon coating on the surface, thereby significantly enhancing the structural integrity of the silicon oxide negative electrode material during the charging and discharging process. During the embedding and de-embedding process of lithium ions, the silicon oxide material will undergo volume expansion and contraction, and the dense carbon coating can effectively alleviate the stress caused by this volume change, thereby helping to improve the problem of volume expansion and contraction when used as a negative electrode material.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A silicon oxide-based negative electrode material is prepared by the following steps:

[0008] Step 1: Add silicon dioxide with a particle size of 200-300 nm, hydrogen peroxide with a mass fraction of 30-40%, and concentrated sulfuric acid with a mass fraction of 75-80% into a reaction kettle, heat to 120-130°C, stir at a speed of 500-700 r / min for 20-30 minutes, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 60-80°C for 1-2 hours to obtain pure silicon dioxide powder;

[0009] Place pure silicon oxide powder in PECVD (plasma chemical vapor deposition equipment), introduce nitrous oxide gas at a flow rate of 50-55mL / min for 10-12min, heat to 400-500℃, form nitrous oxide plasma under the conditions of 200-300W power and 65-68Pa pressure, bombard the pure silicon oxide powder for 20-30min, then wash the bombarded powder with deionized water for 2-3 times to remove impurities, and vacuum dry at 60-80℃ for 1-2h to obtain modified porous silicon oxide powder with a large amount of nitrogen element attached.

[0010] Step 2: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, dimethyl sulfoxide, N,N-dimethylformamide, 6 mol / L acetic acid solution and deionized water into a reactor, stir at 20-25°C and 500-700 r / min for 30-50 min, add lithium sulfate into the reactor, heat to 60-75°C, stir at 500-600 r / min for 1-2 h, and obtain a lithium complex sol with a colloidal particle diameter of 90-100 nm.

[0011] Step 3: Add the lithium complex sol and modified porous silicon oxide powder into the reactor, ultrasonically disperse for 40-60 minutes, stir the reaction at 60-75°C and 500-600r / min for 1.5-2h, cool naturally, filter, wash the filter cake with 3-4L deionized water for 3-5 times, and vacuum dry at 60-80°C for 1-2h to obtain porous silicon oxide complex powder.

[0012] Step 4: Add porous silicon dioxide composite powder and deionized water into a reactor, dissolve sodium hexadecyl sulfate as a surfactant in 70% ethanol aqueous solution and add it into the reactor, stir at 40-50°C and 400-500r / min for 20-30min, add 5-hydroxyisophthalic acid into the reactor, heat to 65-70°C for reaction for 12-14h, filter, wash the filter cake with deionized water, and vacuum dry at 60-80°C for 18-20h to obtain a precursor powder.

[0013] Step 5: Place the precursor powder in a muffle furnace, keep it warm for 2-4 hours under nitrogen protection and at 950-1000°C to carbonize the organic matter in the precursor powder, and cool it naturally to obtain a silicon oxide-based negative electrode material containing a dense carbon coating layer.

[0014] Furthermore, in step 1, the dosage ratio of silicon dioxide, hydrogen peroxide and concentrated sulfuric acid is 500-600 g: 1.5-1.8 L: 900-1000 mL.

[0015] Furthermore, in step 2, the usage ratio of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, dimethyl sulfoxide, N,N-dimethylformamide, acetic acid solution, deionized water and lithium sulfate is 200-250g: 250-260g: 350-360mL: 350-360mL: 120-130mL: 2-2.5L: 200-300g.

[0016] Furthermore, in step three, the usage ratio of the lithium complex sol to the modified porous silicon oxide powder is 500-600 mL: 300-350 g.

[0017] Furthermore, in step 4, the usage ratio of the porous silicon oxide composite powder, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, 5-hydroxyisophthalic acid and lithium sulfate is 250-300 g: 1.5-2 L: 150-160 g: 600-700 mL: 280-290 g: 200-220 g.

[0018] The present invention also provides an application of a silicon oxide-based negative electrode material in preparing a negative electrode for a lithium battery.

[0019] Beneficial effects of the present invention:

[0020] 1. The two coating layers prepared by the present invention form a dense carbon coating layer after high-temperature carbonization, which significantly enhances the structural integrity of the silicon oxide negative electrode material during the charge and discharge process. During the embedding and de-embedding process of lithium ions, the silicon oxide material will expand and shrink in volume, and the dense carbon coating layer can effectively alleviate the stress caused by this volume change, and can significantly improve the conductivity of the silicon oxide negative electrode material; the dense carbon coating layer can effectively optimize the formation of the SEI (solid electrolyte interface) film, making it more stable, reducing the repeated generation and rupture of the SEI film, improving the initial coulomb efficiency, and helping to maintain the capacity and performance stability of the battery.

[0021] 2. The modified porous silicon oxide powder prepared by the present invention, during the plasma bombardment process, the nitrogen ions and oxygen ions in the nitrous oxide plasma collide with the atoms on the surface of the silicon oxide, causing the atoms or molecules on the surface to gain energy and be displaced or sputtered, and some nitrogen atoms and oxygen atoms will chemically react with the silicon atoms on the surface of the silicon oxide. This collision and sputtering process will produce defects and pores on the surface of the silicon oxide, thereby forming a porous structure. At the same time, the N element is doped in the generated carbon layer, thereby improving the conductivity and lithium storage capacity.

[0022] 3. Porosity can accommodate more lithium ions for embedding and de-embedding, and also helps to alleviate the volume effect of the material during the electrochemical reaction, thereby extending the cycle life of the battery. The porous structure of silicon oxide negative electrode material has a larger specific surface area, which is conducive to the diffusion of lithium ions and the transmission of electrons. During the charging and discharging process of lithium-ion batteries, the negative electrode material will expand and shrink in volume. The porous structure of silicon oxide negative electrode material can buffer this volume change through its porosity, thereby maintaining the stability of the electrode structure.

[0023] 4. In the porous silicon oxide composite powder prepared by the present invention, the carboxyl groups on the surface of the lithium composite sol react with the hydroxyl groups on the surface of the modified porous silicon oxide powder, and the particle size of the colloidal particles is smaller than the particle size of the modified porous silicon oxide powder particles. The colloidal particles are adsorbed on the surface of the modified porous silicon oxide powder particles to form a first coating layer, and the lithium in the sol state will penetrate into the interior of the silicon oxide to form lithium silicate salt, which plays a role in lithium supplementation. The first coating layer can effectively inhibit the growth of lithium dendrites, which may cause internal short circuit of the battery, increase the surface area of ​​the negative electrode, and cause the newly exposed lithium to continuously react with the electrolyte, thereby improving the cycle life and coulomb efficiency of the battery. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1: A silicon oxide-based negative electrode material is prepared by the following steps:

[0026] S1: 500 g of silicon oxide with a particle size of 200-300 nm, 1.5 L of 30% hydrogen peroxide and 900 mL of 75% concentrated sulfuric acid were added into a reactor, heated to 120°C, stirred at 500 r / min for 20 min, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 60°C for 1 h to obtain pure silicon oxide powder;

[0027] 450g of pure silicon oxide powder was placed in a PECVD (plasma chemical vapor deposition equipment), nitrous oxide gas was introduced at a flow rate of 50mL / min for 10 minutes, heated to 400°C, and nitrous oxide plasma was formed under the conditions of 200W power and 65Pa pressure to bombard the pure silicon oxide powder for 20 minutes. The bombarded powder was then washed twice with deionized water to remove impurities, and vacuum dried at 60°C for 1 hour to obtain modified porous silicon oxide powder with a large amount of nitrogen element attached.

[0028] During the plasma bombardment process, nitrogen ions and oxygen ions in the nitrous oxide plasma collide with atoms on the surface of silicon oxide, causing the atoms or molecules on the surface to gain energy and be displaced or sputtered. This collision and sputtering process will produce defects and pores on the surface of silicon oxide, thereby forming a modified porous silicon oxide powder with N attached.

[0029] S2: 200g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 250g of 2,5-diaminobenzoic acid, 350mL of dimethyl sulfoxide, 350mL of N,N-dimethylformamide, 120mL of 6mol / L acetic acid solution and 2L of deionized water were added to a reactor, stirred at 20°C and 500r / min for 30min, 200g of lithium sulfate was added to the reactor, heated to 60°C, stirred at 500r / min for 1h, and the hydroxyl and carboxyl functional groups in the reaction monomers were ion exchanged with lithium ions to obtain a lithium complex sol with a colloidal particle diameter of 90-110nm.

[0030] S3: Add 500 mL of lithium complex sol and 300 g of modified porous silicon oxide powder into a reactor, perform ultrasonic dispersion for 40 min, stir and react at 60°C and 500 r / min for 1.5 h, cool naturally, filter, wash the filter cake with deionized water three times, and vacuum dry at 60°C for 1 h to obtain porous silicon oxide complex powder.

[0031] During the reaction, the carboxyl groups on the surface of the lithium complex sol colloidal particles react with the hydroxyl groups on the surface of the modified porous silica powder. Since the particle size of the colloidal particles is smaller than that of the modified porous silica powder particles, the colloidal particles are adsorbed on the surface of the modified porous silica powder particles to form a first coating layer, and the lithium in the colloidal particles in the sol state will form lithium silicate salt with silica, which plays a role in lithium supplementation.

[0032] S4: 250 g of porous silicon dioxide composite powder and 1.5 L of deionized water were added to a reactor, 150 g of sodium hexadecyl sulfate as a surfactant was dissolved in 600 mL of 70% ethanol aqueous solution and added to the reactor, stirred at 40°C and 400 r / min for 20 min, 280 g of 5-hydroxyisophthalic acid was added to the reactor, heated to 65°C and reacted for 4 h, 200 g of lithium sulfate was added to the reactor, the reaction was continued for 4 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 60°C for 18 h to obtain a precursor powder.

[0033] The carboxyl groups on the surface of the porous silicon oxide composite powder react with the hydroxyl groups of 5-hydroxyisophthalic acid to generate a skeleton with high specific surface area and structural diversity, which is wrapped on the surface to form a second coating layer.

[0034] S5: The precursor powder is placed in a muffle furnace, and kept warm at 950°C for 2 hours under nitrogen protection to carbonize the organic matter in the precursor powder, and then cooled naturally to obtain a silicon oxide-based negative electrode material containing a dense carbon coating layer.

[0035] Example 2: A silicon oxide-based negative electrode material is prepared by the following steps:

[0036] S1: 550 g of silicon oxide with a particle size of 200-300 nm, 1.6 L of 35% hydrogen peroxide and 950 mL of 80% concentrated sulfuric acid were added into a reactor, heated to 125°C, stirred at 600 r / min for 25 min, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 70°C for 1.5 h to obtain pure silicon oxide powder;

[0037] 470g of pure silicon oxide powder was placed in a PECVD (plasma chemical vapor deposition equipment), and nitrous oxide gas was introduced at a flow rate of 53mL / min for 11 minutes. The mixture was heated to 450°C, and nitrous oxide plasma was formed under the conditions of 250W power and 66Pa pressure. The pure silicon oxide powder was bombarded for 25 minutes. The bombarded powder was then washed twice with deionized water to remove impurities, and vacuum dried at 75°C for 1.5 hours to obtain modified porous silicon oxide powder with a large amount of nitrogen elements attached.

[0038] During the plasma bombardment process, nitrogen ions and oxygen ions in the nitrous oxide plasma collide with atoms on the surface of silicon oxide, causing the atoms or molecules on the surface to gain energy and be displaced or sputtered. This collision and sputtering process will produce defects and pores on the surface of silicon oxide, thereby forming a modified porous silicon oxide powder with N attached.

[0039] S2: 230g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 255g of 2,5-diaminobenzoic acid, 355mL of dimethyl sulfoxide, 355mL of N,N-dimethylformamide, 125mL of 6mol / L acetic acid solution and 2.3L of deionized water were added to a reactor, stirred at 22°C and 600r / min for 40min, 250g of lithium sulfate was added to the reactor, heated to 70°C, stirred at 550r / min for 1.5h, and the hydroxyl and carboxyl functional groups in the reaction monomers were ion-exchanged with lithium ions to obtain a lithium complex sol with a colloidal particle diameter of 90-110nm.

[0040] S3: Add 550 mL of lithium complex sol and 320 g of modified porous silicon oxide powder into a reactor, perform ultrasonic dispersion for 50 min, stir and react at 70°C and 550 r / min for 1.8 h, cool naturally, filter, wash the filter cake with deionized water 4 times, and vacuum dry at 70°C for 1.5 h to obtain porous silicon oxide complex powder.

[0041] During the reaction, the carboxyl groups on the surface of the lithium complex sol colloidal particles react with the hydroxyl groups on the surface of the modified porous silica powder. Since the particle size of the colloidal particles is smaller than that of the modified porous silica powder particles, the colloidal particles are adsorbed on the surface of the modified porous silica powder particles to form a first coating layer, and the lithium in the colloidal particles in the sol state will form lithium silicate salt with silica, which plays a role in lithium supplementation.

[0042] S4: 270 g of porous silicon dioxide composite powder and 1.8 L of deionized water were added to a reactor, 155 g of sodium hexadecyl sulfate as a surfactant was dissolved in 650 mL of 70% ethanol aqueous solution and added to the reactor, stirred at 45°C and 450 r / min for 25 min, 285 g of 5-hydroxyisophthalic acid was added to the reactor, heated to 68°C for reaction for 5 h, 210 g of lithium sulfate was added to the reactor, the reaction was continued for 5 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 70°C for 19 h to obtain a precursor powder.

[0043] The carboxyl groups on the surface of the porous silicon oxide composite powder react with the hydroxyl groups of 5-hydroxyisophthalic acid to generate a skeleton with high specific surface area and structural diversity, which is wrapped on the surface to form a second coating layer.

[0044] S5: The precursor powder is placed in a muffle furnace, and kept warm at 980°C for 3 hours under nitrogen protection to carbonize the organic matter in the precursor powder, and then cooled naturally to obtain a silicon oxide-based negative electrode material containing a dense carbon coating layer.

[0045] Example 3: A silicon oxide-based negative electrode material is prepared by the following steps:

[0046] S1: 600 g of silicon oxide with a particle size of 200-300 nm, 1.8 L of 40% hydrogen peroxide and 1000 mL of 80% concentrated sulfuric acid were added into a reactor, heated to 130°C, stirred at 700 r / min for 30 min, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 80°C for 2 h to obtain pure silicon oxide powder;

[0047] 500g of pure silicon oxide powder was placed in a PECVD (plasma chemical vapor deposition equipment), nitrous oxide gas was introduced at a flow rate of 55mL / min for 12min, heated to 500°C, and nitrous oxide plasma was formed under the conditions of 300W power and 68Pa pressure to bombard the pure silicon oxide powder for 30min. The bombarded powder was then washed three times with deionized water to remove impurities, and vacuum dried at 80°C for 2h to obtain modified porous silicon oxide powder with a large amount of nitrogen element attached.

[0048] During the plasma bombardment process, nitrogen ions and oxygen ions in the nitrous oxide plasma collide with atoms on the surface of silicon oxide, causing the atoms or molecules on the surface to gain energy and be displaced or sputtered. This collision and sputtering process will produce defects and pores on the surface of silicon oxide, thereby forming a modified porous silicon oxide powder with N attached.

[0049] S2: 250g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 260g of 2,5-diaminobenzoic acid, 360mL of dimethyl sulfoxide, 360mL of N,N-dimethylformamide, 130mL of 6mol / L acetic acid solution and 2.5L of deionized water were added to a reactor, stirred at 25°C and 700r / min for 50min, 300g of lithium sulfate was added to the reactor, heated to 75°C, stirred at 600r / min for 2h, and the hydroxyl and carboxyl functional groups in the reaction monomers were ion-exchanged with lithium ions to obtain a lithium complex sol with a colloidal particle diameter of 90-110nm.

[0050] S3: Add 600 mL of lithium complex sol and 350 g of modified porous silicon oxide powder into a reactor, perform ultrasonic dispersion for 60 min, stir and react at 75 ° C and 600 r / min for 2 h, cool naturally, filter, wash the filter cake with deionized water 5 times, and vacuum dry at 80 ° C for 2 h to obtain porous silicon oxide complex powder.

[0051] During the reaction, the carboxyl groups on the surface of the lithium complex sol colloidal particles react with the hydroxyl groups on the surface of the modified porous silica powder. Since the particle size of the colloidal particles is smaller than that of the modified porous silica powder particles, the colloidal particles are adsorbed on the surface of the modified porous silica powder particles to form a first coating layer, and the lithium in the colloidal particles in the sol state will form lithium silicate salt with silica, which plays a role in lithium supplementation.

[0052] S4: 300 g of porous silicon oxide composite powder and 2 L of deionized water were added to a reactor, 160 g of sodium hexadecyl sulfate as a surfactant was dissolved in 700 mL of 70% ethanol aqueous solution and added to the reactor, stirred at 50°C and 500 r / min for 30 min, 290 g of 5-hydroxyisophthalic acid was added to the reactor, heated to 70°C for reaction for 6 h, 220 g of lithium sulfate was added to the reactor, the reaction was continued for 6 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 80°C for 20 h to obtain a precursor powder.

[0053] The carboxyl groups on the surface of the porous silicon oxide composite powder react with the hydroxyl groups of 5-hydroxyisophthalic acid to generate a skeleton with high specific surface area and structural diversity, which is wrapped on the surface to form a second coating layer.

[0054] S5: placing the precursor powder in a muffle furnace, keeping it warm for 4 hours under nitrogen protection and at 1000°C, carbonizing the organic matter in the precursor powder, and cooling it naturally to obtain a silicon oxide-based negative electrode material containing a dense carbon coating layer.

[0055] Comparative Example 1: Based on Example 3, the modified porous silicon oxide powder in step S3 is replaced by the raw silicon oxide (particle size of 200-300 nm) in step S1, and the other steps remain unchanged to prepare a silicon oxide negative electrode material.

[0056] Comparative Example 2: Based on Example 3, the lithium sulfate in step S2 is replaced with commercially available lithium powder, and the other steps remain unchanged to prepare a silicon oxide negative electrode material.

[0057] Comparative Example 3: Based on Example 3, the precursor powder in step S5 is replaced with silicon oxide (particle size is 200-300nm), and the mixture is kept warm at 1000°C for 4 hours under the protection of acetylene and nitrogen. A mixed gas of acetylene and nitrogen is introduced with a volume ratio of acetylene to nitrogen of 1:19 to carbonize the acetylene and carbon-coate the silicon oxide to prepare a silicon oxide negative electrode material.

[0058] The model of PECVD (plasma chemical vapor deposition equipment) is OTF-1200X-III-S-3CL.

[0059] The sources of some reagents in the embodiments and comparative examples are as follows:

[0060] 1,3,6,8-Tetrakis(4-formaldehydephenyl)-pyrene was purchased from Xi'an Qiyue Biotechnology Co., Ltd.

[0061] 2,5-Diaminobenzoic acid was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0062] Dimethyl sulfoxide, N,N-dimethylformamide, acetic acid solution, lithium sulfate, sodium hexadecyl sulfate, and 5-hydroxyisophthalic acid were purchased from Sigma-Aldrich.

[0063] The silicon oxide-based negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare lithium battery negative electrodes for performance testing. 2 g of the prepared silicon oxide-based negative electrode materials were placed in a powder resistivity tester and the pressure was set to 20 MPa for powder resistivity testing.

[0064] The prepared silicon oxide-based negative electrode material, carbon black and carboxymethyl cellulose (CMC) were mixed with styrene-butadiene rubber (SBR) composite binder in a mass ratio of 8:2:1 to form a slurry, which was evenly coated on a copper foil current collector and vacuum dried for 12 hours to form a working electrode. A lithium sheet was used as a counter electrode, a glass fiber membrane (purchased from Whatman, UK) was used as a separator, and 1 mol / L lithium tetrafluoroborate (the solvent was methoxyethane and ethylene carbonate in a volume ratio of 1:1) was used as an electrolyte. 1% of vinylene carbonate and 5% of fluoroethylene carbonate were added to the electrolyte, and button cells were assembled in an argon atmosphere in a Braun inert gas glove box in Germany.

[0065] An in-situ volume monitor (GVM2200) was used to monitor the volume change of the battery in real time during the charge and discharge process. The charge and discharge test of the button battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. The charge and discharge voltage was limited to 0.05-1.5V. The first charge and discharge performance test was carried out at room temperature, with a constant current of 0.1C. After 10 cycles, it was switched to a constant current of 0.5C for 100 cycles. The capacity retention rate was calculated. The results are shown in Table 1:

[0066] Table 1

[0067] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Conductivity (S / cm) 31.7 33.6 35.2 18.0 25.3 17.3 100 cycles capacity retention rate (%) 94.2 94.4 94.5 83.5 85.2 82.2 First efficiency (%) 96.5 98.7 99.1 87.2 89.6 84.3 Volume change percentage (%) 80 75 70 110 90 115 First discharge capacity (mAh / g) 1500.8 1528.2 1539.4 1390.3 1421.7 1269.6

[0068] It can be seen from Table 1 that the electrical conductivity of the silicon oxide-based negative electrode materials prepared in Examples 1 to 3 of the present invention is significantly better than that of the comparative example. During the plasma bombardment process, the nitrogen ions and oxygen ions in the nitrous oxide plasma collide with the atoms on the surface of the silicon oxide, causing the atoms or molecules on the surface to gain energy and be displaced or sputtered, thereby forming a porous structure. At the same time, the N element is doped in the generated carbon layer, which improves the electrical conductivity. In Comparative Example 1, the modified porous silicon oxide powder is replaced with the raw silicon oxide in step S1. Compared with the porous structure, the raw silicon oxide has a smaller specific surface area, provides limited charge transfer paths and reaction sites, limits the electrical conductivity, and is less likely to occur during the lithium insertion process. Volume expansion is prone to occur, resulting in poor cycle capacity; the cycle capacity of Examples 1 to 3 is significantly better than that of the comparative example, the porosity can accommodate more lithium ions for embedding and de-embedding, and also helps to alleviate the volume effect of the material during the electrochemical reaction, and the formation of the first coating layer can effectively inhibit the growth of lithium dendrites, thereby extending the cycle life of the battery; the first efficiency, volume change percentage and first discharge capacity of Examples 1 to 3 are significantly better than those of the comparative example, in Comparative Example 2, lithium sulfate is replaced with commercially available single lithium powder, and single lithium cannot be evenly dispersed in the lithium composite sol, and thus cannot form a uniform and dense first coating layer on the surface of the modified porous silicon oxide powder particles.

[0069] The prepared silicon oxide-based negative electrode material has porosity and a two-layer dense carbon coating structure, which can effectively optimize the formation of the SEI (solid electrolyte interface) film, making it more stable, reducing the repeated generation and rupture of the SEI film, and improving the first coulombic efficiency; the larger specific surface area and porosity help to increase the storage capacity and active sites of lithium ions, thereby improving the first discharge capacity.

[0070] In Comparative Example 3, the precursor powder is replaced with silicon oxide, and the silicon oxide is carbon-coated by acetylene carbonization to form a single carbonization layer, resulting in low coating of the silicon oxide and failure to effectively relieve the stress caused by volume change. The resulting silicon oxide negative electrode material has poor conductivity, low first coulomb efficiency and first discharge capacity.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a silicon oxide-based negative electrode material, characterized in that: Prepared by the following steps: Step 1: placing pure silicon oxide powder in a plasma chemical vapor deposition device, introducing nitrous oxide gas, forming nitrous oxide plasma under the conditions of 200-300W power and 65-68Pa pressure, bombarding the pure silicon oxide powder for 20-30min, washing with deionized water, and vacuum drying at 60-80℃ for 1-2h to obtain modified porous silicon oxide powder; Step 2: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, dimethyl sulfoxide, N,N-dimethylformamide, 6 mol / L acetic acid solution and deionized water into a reaction kettle, stir at 20-25°C and 500-700 r / min for 30-50 min, add lithium sulfate into the reaction kettle, stir at 60-75°C and 500-600 r / min for 1-2 h, and obtain a lithium complex sol with a colloidal particle diameter of 90-100 nm; Add the lithium complex sol and the modified porous silicon oxide powder into a reaction kettle, perform ultrasonic dispersion for 40-60 minutes, stir and react at 60-75° C. and 500-600 r / min for 1.5-2 hours, cool naturally, filter by suction, wash the filter cake with deionized water for 3-5 times, and vacuum dry at 60-80° C. for 1-2 hours to obtain a porous silicon oxide complex powder; Step 3: Add porous silicon oxide composite powder and deionized water into a reactor, dissolve sodium hexadecyl sulfate in 70wt% ethanol aqueous solution and add into the reactor, stir at 40-50°C and 400-500r / min for 20-30min, add 5-hydroxyisophthalic acid into the reactor, heat to 65-70°C and react for 4-6h, then add lithium sulfate into the reactor, continue to react for 4-6h, filter, wash the filter cake with deionized water, and vacuum dry at 60-80°C for 18-20h to obtain a precursor powder; Step 4: Place the precursor powder in a muffle furnace, keep it warm for 2-4 hours under nitrogen protection and at 950-1000°C, and cool it naturally to obtain a silicon oxide-based negative electrode material.

2. The method for preparing a silicon oxide-based negative electrode material according to claim 1, characterized in that: The pure silicon oxide powder in step 1 is prepared by the following steps: Add silicon oxide with a particle size of 200-300 nm, 30-40wt% hydrogen peroxide and 75-80wt% concentrated sulfuric acid into a reactor, stir at 120-130°C and 500-700r / min for 20-30min, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 60-80°C for 1-2h to obtain pure silicon oxide powder.

3. The method for preparing a silicon oxide-based negative electrode material according to claim 2, characterized in that: The usage ratio of silicon dioxide, hydrogen peroxide and concentrated sulfuric acid is 500-600 g: 1.5-1.8 L: 900-1000 mL.

4. The method for preparing a silicon oxide-based negative electrode material according to claim 1, characterized in that: The usage ratio of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, dimethyl sulfoxide, N,N-dimethylformamide, acetic acid solution, deionized water and lithium sulfate in step 2 is 200-250g: 250-260g: 350-360mL: 350-360mL: 120-130mL: 2-2.5L: 200-300g.

5. The method for preparing a silicon oxide-based negative electrode material according to claim 1, characterized in that: In step 2, the usage ratio of the lithium complex sol and the modified porous silicon oxide powder is 500-600 mL: 300-350 g.

6. The method for preparing a silicon oxide-based negative electrode material according to claim 1, characterized in that: The usage ratio of the porous silicon oxide composite powder, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, 5-hydroxyisophthalic acid and lithium sulfate in step 3 is 250-300g: 1.5-2L: 150-160g: 600-700mL: 280-290g: 200-220g.

7. A silicon oxide-based negative electrode material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 6.

8. Use of the silicon oxide-based negative electrode material according to claim 7 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Magnesium-doped silicon monoxide composite negative electrode material and preparation method thereof

    CN116081632A

  • PERC battery back multilayer film structure and preparation method thereof

    CN115842061A

  • KR20210025924A